EFEKTIVITAS EKSTRAK KULIT BATANG MAJA (Aegle marmelos L) TERHADAP KEMATIAN LARVA NYAMUK Anopheles sp. - Pratama, Sinta Debi; Yushananta, Prayudhy (Poltekkes Kemenkes Tanjung Karang, 2021)
Malaria is one of the public health problems that can cause death in infants, children under five, pregnant women and reduces work productivity. Vector control by chemical means leads to vector resistance and environmental pollution and negatively impacts public and animal health. This study aims to determine the effectiveness of the bark extract of Maja (Aegle marmelos L) against the death of Anopheles sp mosquito larvae with concentrations of 5%, 10%, 20%, 40%, and 50% and the observation of contact times every 15 minutes, 30 minutes, 60 minutes, 90 minutes and 120 minutes. The study used a Completely Randomized Design (CRD) with Factorial. Extraction used maceration method, with 70% ethanol as solvent. Larvae of Anopheles sp. instar III obtained from malaria endemic area. The test used a 200 ml container, with two replications. All data were analyzed by two way ANOVA and Tukey HSD test. This study obtained mortality of 93.3% larvae at a concentration of 50% and a contact time of 120 minutes. The results of statistical analysis showed a significant effect of concentration (p=0.0001), contact time (p=0.0001), and interaction concentration-contact time (p=0.004) on the mortality of Anopheles sp. mosquito larvae. This study has proven the use of bark extract of Maja (Aegle marmelos L) as an alternative bio-insecticide in controlling mosquito larvae of Anopheles sp.